Comparison of the Wake-up Test and Combined TES-MEP and CSEP Monitoring in Spinal Surgery. Issue 9 (November 2015) - Chen, Bailing; Chen, Yuguang; Yang, Junlin; Xie, Denghui; Su, Haihua; Li, Fobao; Wan, Yong; Peng, Xinsheng; Zheng, Zhaomin
Abstract : Study Design: A retrospective clinical analysis. Objective: The aim of this study was to compare the effectiveness of the wake-up test with that of combined monitoring of transcranial electrical stimulation motor evoked potentials (TES-MEP) and cortical somatosensory evoked potentials (CSEP) in spinal surgery. Summary of Background Data: TES-MEP/CSEP combined monitoring is being increasingly recognized as the ideal approach to detect spinal neurophysiological compromise during spinal surgery; however, as a result the merit of the wake-up test is now in doubt. Materials and Methods: TES-MEP/CSEP combined monitoring was performed simultaneously in 426 patients who underwent spinal surgery at our department, and wake-up tests were conducted on 23 patients because of positive neurophysiological monitoring results with uncertain causes or persistent positive monitoring findings after all potential causes had been resolved. Preoperative and postoperative neurological examinations were performed as the gold standard to detect irreversible spinal function compromise. All data were collected to compare the efficiency of TES-MEP/CSEP combined monitoring with that of the wake-up test. Results: Positive results of TES-MEP/CSEP combined monitoring were recorded in 64 cases. Among them, the positive monitoring findings agreed with the results of the neurological examination in 51 cases, and the monitoring results did not match that of neurological examination in 13 cases. No false-negative result was observed. The sensitivity of TES-MEP/CSEP monitoring was 100%, the specificity was 96.5%, and the Youden index was 0.965. Wake-up tests were conducted in 23 cases. In 8 patients the positive monitoring findings completely matched the postoperative neurological examination results. In contrast, in the other 15 cases with negative neurophysiological monitoring results, only 9 patients retained intact neurological function and 6 patients suffered compromised neurological function. The sensitivity of the wake-up test was 57.1%, the specificity was 100%, and the Youden index was 0.571. Conclusions: Combined TES-MEP and CSEP monitoring, with its high sensitivity and specificity, is an effective method for monitoring spinal function during surgery and should be the preferred choice. The wake-up test is a useful complementary method for monitoring because of its high specificity.